Popularizing and Translating Science in 18th-century Europe: Francesco Algarotti’s Newtonianismo per le dame and its English-language Editions (1737-1772) - Vicentini, Alessandra (Status Quaestionis, 2019)
Francesco Algarotti’s Newtonianismo per le dame (1737) played a significant role in the popularization of Newton(ianism) on the Continent and in Britain in the 18th century. Compiled as a seduction manual for ladies after the fashion of contemporary poems and novels, it targeted the largest possible lay audience in order to gain potential advocates for the new experimental science and to covertly denounce Italy’s stagnant political, social, and cultural condition. This study discusses some of the most recent scholarly interpretations the text and its four English issues (1739, 1742, 1765, and 1772) have so far received, explaining how it was transmitted differently in Italy and in Britain. It then examines the linguistic popularizing strategies, focusing especially upon the terminology employed by Algarotti to address a lay audience and its English-language rendering in Elizabeth Carter’s first English translation (1739). Results show that diverse popularizing techniques were employed, which were mainly translated into English literally by Carter, although some important instances of adaptation and reformulation emerge revealing precise strategies not only to further simplify the text but also to accommodate it to a different readership and separate aims. The investigation combines methods derived from (Critical) discourse analysis (Fairclough 2013; Gee 2014) and historical pragmatics (Culpeper and Kÿto 2010). Studies of popularization strategies (Garzone 2006), English for scientific purposes (Gotti 1992, 2011, 2013), English historical linguistics (Bergs and Brinton 2012), and models of translation analysis (Vinay and Darbelnet 1958; Reiss 1976; Newmark 1988; Baker and Saldanha 2011) are also referred to.